Design and development of a tabletop indoor herb or vegetable planter box - Bahjah Binte Mohamed Yamin (Nanyang Technological University, 2024)
Agriculture is an essential part of human civilisation. Humans have long used agricultural practices to produce the food they need to survive. Due to this, it is always being analysed and researched to develop methods that are more efficient and produce higher yields. However, in today’s urban jungle, it is difficult grow produce in limited spaces. Therefore, this project aims to create a table top planter box that will allow vegetables or herbs to flourish indoors. This report will first examine different agricultural methods, different materials and plant growth factors. Afterwards, a planter box design will be developed, created and tested. Lastly, the project will review the design’s effectiveness, its limitations and further improvements that can be made.